Reduction of the Pollutant Load of Textile Wastewater Using Chitosane as Natural Coagulant, Huancayo - 2020-2021 - Caballero Blanco, Claudia Milagros (2024)
Industrial effluents have high pollutant loads depending on the type of industry that generates them, which makes their treatment difficult. The textile industry consumes large amounts of water, generating large volumes of wastewater with high turbidity concentrations. For this reason, the main objective of the research was to analyse the efficiency of chitosan in reducing the pollutant load of industrial textile effluents in the city of Huancayo in the year 2020 - 2021. Tests were carried out following the guidelines of an experimental design with a pre-test, post-test, and a control group. There were 3 treatments with 160, 180, and 200 mg/L doses. An optimum efficient turbidity removal of 47.17 % was achieved at a dosage of 160 mg/L without causing variations in the effluent pH.